(untitled) (Nordic Journal of African Studies, 2003)
Samo, an Eastern Mande language, is insularly enclosed predominantly by Gur languages. Considering the fact that Samo has close contact with several dominant languages intense language borrowing should be likely. However, a comparison of lexical data from the respective languages (the lingua franca Moore, Lele, the lingua franca Jula, Marka, Southern and Northern Samo) revealed no strong contact phenomena between Samo and any of the contact languages. Therefore, the position of Samo as a language island is confirmed and newly classified within Keuthmann, Schreiber & Vossen’s (in press) framework as an island language. However, the question of the position of Marka, Samo’s related neighbour to the west, within a language island or island language concept remains to be solved. Marka, does not exhibit sufficient lexical agreement with Samo to be classified as part of one larger language island but is, nevertheless, clearly related to Samo. A new subcategory of island language, a twin-island language, is, therefore, proposed.